Late‐summer biogeochemistry in the Mertz Polynya: East Antarctica. Issue 9 (13th September 2017) - Shadwick, E. H.; Tilbrook, B.; Currie, K. I.
Abstract: A marked reconfiguration of the Mertz Polynya following the 2010 calving of the Mertz Glacier Tongue has been associated with a decrease in the size and activity of the polynya. We report observations of the oceanic carbonate (CO2 ) system in late‐summer 2013, the third post‐calving summer season. Estimates of seasonal net community production (NCP) based on inorganic carbon deficits and the oxygen‐argon ratio indicate that the waters on the shelf to the east of Commonwealth Bay (adjacent to the Mertz Glacier) remain productive compared to pre‐calving conditions. The input of residual or excess alkalinity from melting sea ice is found to contribute to the seasonal enhancement of carbonate saturation state and pH in shelf waters. Mean rates of NCP in 2012–2013 are more than twice as large as those observed in the pre‐calving summers of 2001 and 2008 and suggest that the new (post‐calving) configuration of the polynya favors enhanced net community production and a stronger surface ocean sink for atmospheric CO2 due at least in part to the redistribution of sea ice and associated changes in summer surface stratification. Key Points: Enhanced net community production persists 3 years after Mertz Glacier calving New polynya configuration appears to favor enhanced surface ocean CO2 uptake Surface CO2 undersaturation in the eastern shelf and slope appears supported by input of residual or excess alkalinity from melting sea ice